2020
DOI: 10.18421/tem93-49
|View full text |Cite
|
Sign up to set email alerts
|

Development of Foreign Language Teachers' Diagnostic Competence in the System of Military Education

Abstract: The article is dedicated to the problem of foreign language teachers' diagnostic competence development. It reveals the problematic issues connected with the obtaining integral estimates of students' foreign language communicative competence formation levels. The study presents a technology of integrated assessment based on the recent mathematical and statistical methods realized with the help of information and communication technologies. The first experiment proves the technology contributes to the accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…During the full-time study, the predominant type of training was practical training, which ensures the implementation of the didactic principle of linking theory with practice, deepening, systematisation, consolidation and specification of knowledge gained in lectures and the process of independent work; formation of practical skills and abilities necessary for professional activity; development of skills to observe and explain certain scientific, educational and scientific phenomena under study; formation and development of practical, professional thinking; development of independence in learning activities, etc. (Yahupov et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…During the full-time study, the predominant type of training was practical training, which ensures the implementation of the didactic principle of linking theory with practice, deepening, systematisation, consolidation and specification of knowledge gained in lectures and the process of independent work; formation of practical skills and abilities necessary for professional activity; development of skills to observe and explain certain scientific, educational and scientific phenomena under study; formation and development of practical, professional thinking; development of independence in learning activities, etc. (Yahupov et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Objectivity is a fundamental problem in the system of physical education and sport. In order to objectively compare one level of achievement with another level, it is what is achieved that must be measured using means containing predetermined units of measurement [19]. To a great extent the effectiveness of their combat activity depends on the objectivity of the implementation of Tolerance (from Latin tolerantiapatience) is respect, acceptance, and proper understanding by future officers as specialists in physical training and sports without aggression of different opinions, as well as tolerance to the features of behavior, customs, feelings, beliefs and lifestyles of others, which affects the military-professional and physical types of ability to qualitatively perform diagnostic activities with the personnel.…”
Section: постановкаmentioning
confidence: 99%
“…The analysis of Ukrainian scientific researches and scientific researches from other countries has shown that the professional competence of a military specialist is a professional and personal phenomenon formed in the process of officers’ professional training in HMEI and revealed itself, developed and improved during their professional military activity, and the efficiency of this activity depends on the officers’ theoretical, practical and psychological readiness and on their personal, professional and psychological qualities and values (Yahupov et al, 2020). Due attention was paid to revealing officers’ FLCC essence.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…The training of a competent, competitive specialist on the labour market is an important task of the education system, in connection with which the development of the communicative competence of a cadet at a HMEI is a priority task at that stage of their military education. Higher military education can solve many problems of the development and formation of an individual, including the problem of an officer entering the social world (Matiychak et al, 2019; Yahupov et al, 2020). The issue of military specialists’ training is multi‐dimensional and broad, as evidenced by the increase of scientific investigations in the area of formation of the next generation of officers: responsible, independent, proactive, flexible, able to analyse economic and political situations, take rational decisions and capable to solve the job tasks using ICT (Osodlo et al, 2020; Vitchenko & Osodlo, 2019).…”
Section: Theoretical Overviewmentioning
confidence: 99%